Caracterización socioeconómica y productiva de la parroquia San Buenaventura, cantón Latacunga, provincia de Cotopaxi 2022. - Defaz Defas, Danny Alexis (2022)
This research is based on the “Socioeconomic and productive characterization of the San Buenaventura parish of the Latacunga Canton, Cotopaxi Province 2022,” this study emphasizes the social, economic, and productive diagnosis of the inhabitants of San Buenaventura urban parish to generate reliable information on the life tasks of the inhabitants of the place through a structured survey with qualitative and quantitative modalities, for which a survey based on socioeconomic and productive indicators was applied through the KoboToolbox application that generates a spreadsheet in Excel, where the following results were got: there is a homogeneous number of men and women who have a secondary education level, the inhabitants have their own houses made up of 3 to 4 people of which 1 to 2 children live and older adults, where there is a minimal amount of disability (physical-mental). The economic indicator shows that 60% have their own business, 22% are dedicated to horticultural production, where getting a job is difficult due to the lack of organizations that do not allow the active participation of residents, people maintain essential services, and infrastructure within reach. The productive index indicates a minimum percentage of people dedicated to horticulture; 34% of these have a productive area of 100m2 to 1000 m2, 55% apply organic fertilizers obtained from breeding animals, and they do not use agrochemicals. They do not belong to any organization; they trust the neighborhood president, and they need training from the Technical University of Cotopaxi. It is recommended to manage alternatives that public policies are aimed at strengthening the socio-productive processes of the area, generating sources of work so that they have the opportunity to stay in their own sector.